The political globalisation trilemma revisited: An empirical assessment across countries and over time - Michael Funke; Doudou Zhong (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
The political hyperglobalisation trilemma asserts that a government cannot simultaneously opt for deep international integration, national sovereignty and democratic politics, but rather is constrained to choosing two of the three at most. This paper presents a new and comprehensive cross-country panel dataset operationalising the multifaceted three vertices of the trilemma. After an explorative data analysis, we employ panel error-correction techniques to uncover the mutual interdependencies among the variables in the system. The econometric evidence supports the existence of a long-run relationship between economic integration, national sovereignty and democratic politics as postulated in the political globalisation trilemma.
URN:NBN:fi:bof-202008122274
Keywords: F60; F62; F15; F68; 330; political trilemma; globalisation; democratic politics; national sovereignty